Litterfall and nutrient input in a degraded area - Giácomo, Rômulo Guimarães [UNESP]; Alves, Marlene Cristina [UNESP]; Camara, Rodrigo; Pereira, Marcos Gervasio; de Arruda, Otton Garcia [UNESP]; Souto, Sebastião Nilce [UNESP]; de Moraes, Mário Luis Teixeira [UNESP] (FapUNIFESP (SciELO), 2017)
This study aimed to test the effects of fertilization with organic compost from industrial production of pulp on the litterfall and nutrient input of monospecific plantations in a loan area. The treatments consisted of three doses of the organic compost D10, D15 and D20 (10, 15 and 20 Mg ha-1, respectively), mineral conventional fertilization (DAM) and no fertilization (D0) in land plots (N = 4/treatment/species; 15 x 12 m). Litterfall was monthly collected by two traps (0.72 m2/plot) and sorted out into leaves, twigs, seeds, flowers, fruits and others. We determined the input of nitrogen, phosphorous and potassium. There were no differences among the treatments and between species in terms of total annual litterfall. The higher nutrient input was obtained by DAM, followed by D10, in both plantations. The annual nutrient input was higher for the litterfall on the E. urograndis plantation.
Keywords: Eucalyptus urograndis; Mabea fistulifera; Nutrient cycling